Subjective assessment on vocational training activities: a generalized ordered probit approach - Budría Rodríguez, Santiago (2021)
In this paper, we use self-assessed data from participants in vocational train ing in Madeira to investigate what are the determinants of the effectiveness of the training along three dimensions: employment, job-related skills and produc tivity. We find that respondents score training activities high in every dimension. Moreover, we find that training is more effective among the educated, indicat ing that vocational training is far from being remedial. We also find that long training programs and training in the area of Tourism are particularly effective. The results, based on a Generalized Ordered Probit, uncover the differential ef fect that some characteristics have among individuals who report high and low effectiveness scores.